The perfect storm - Weinstein, Paula; Peterson, Wolfgang ([Burbank, CA] : Warner Bros Pictures, 2001)
The Andrea Gail is a sword fishing boat out of Gloucester, Massachusetts. Billy Tyne is her captain, down-on-his-luck from a recent losing streak, looking to bring back one big score so he and his crew will have the money to stay ashore during the coming winter
Executive producer, Barry Levinson ; screenplay, Bill Wittliff ; editor, Richard Francis-Bruce
Cast: George Clooney, Mark Wahlberg, Diane Lane
VCD format
Keywords: Suspense in motion pictures; Disaster films